2014
DOI: 10.1007/s12094-013-1153-7
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the use of G-CSF and its impact on dose response for anthracycline plus taxane-based schedules in early breast cancer

Abstract: PurposeTo evaluate the impact on survival of the relative dose intensity (RDI) achieved in patients with early breast cancer receiving anthracycline plus taxane-based chemotherapy in the adjuvant setting.Patients and methodsPatients with early breast cancer diagnosed from January 1999 through December 2006 were included. Dose intensity was evaluated according to the number of delayed cycles and days and the percentage of RDI.ResultsA total of 231 breast cancer patients were included. Granulocyte colony-stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…The studies included in the systematic literature review ( n = 22) [5, 16–36] were grouped by chemotherapy regimen. Most studies reported outcomes of OS or PFS.…”
Section: Resultsmentioning
confidence: 99%
“…The studies included in the systematic literature review ( n = 22) [5, 16–36] were grouped by chemotherapy regimen. Most studies reported outcomes of OS or PFS.…”
Section: Resultsmentioning
confidence: 99%
“…Although neutropenia commonly results from cytotoxic chemotherapy and lowering chemotherapy dose intensity may reduce the risk of FN, reductions in chemotherapy dose intensity may compromise long term outcome and shorten overall survival. RCTs as well as observational studies have demonstrated the importance of maintaining chemotherapy dose intensity in the curative setting of ESBC (Bonadonna et al 1995 ; Budman et al 1998 ; Chirivella et al 2009 ; Perez-Fidalgo et al 2014 ). In the study reported here, one-fifth of patients received overall RDI below 85% while 13% started the treatment with planned RDI <85%.…”
Section: Discussionmentioning
confidence: 99%
“…Granulocyte-colony-stimulating factors (G-CSFs) can be used to manage FN, and also as an adjunct to deliver dosedense myelosuppressive regimens [3]. G-CSFs have shown effectiveness in reducing the incidence of FN by decreasing the severity and duration of neutropenia [4][5][6][7][8]. Current clinical guidelines recommend primary prophylaxis (PP) with G-CSF when the overall risk of developing FN is 20% or higher [9][10][11].…”
mentioning
confidence: 99%